The Misconceptions and Determinants of Diabetes Knowledge in Patients with Diabetes in Taiwan - Chia-Chia Chen; Chien-Lung Chen; Yu Ko (Journal of Diabetes Research)
Aim. This study aimed at (1) examining the misconceptions of patients with diabetes in Taiwan and (2) examining the association between patients’ diabetes knowledge and their demographic characteristics. Methods. A cross-sectional survey was conducted at a metropolitan hospital in northern Taiwan. A total of 501 outpatients with diabetes were recruited, mostly from the hospital’s endocrinology and metabolism clinic, nephrology clinic, and dialysis center. A self-developed questionnaire that consisted of demographic information and a diabetes knowledge test was administered. The knowledge test included 10 True/False questions and 6 multiple-choice questions that aimed at identifying patients’ common misconceptions about diabetes. Results. A perfect score on the diabetes knowledge test was 16 points, and the mean±SD score of the respondents was 11.5±2.8. The most common misconception was “People can always feel when their blood sugar level is high.” (64%), followed by “Taking insulin hurts the kidneys and may result in a need for dialysis.” (52%) and “Being a vegetarian helps control blood sugar levels.” (48%). The total knowledge scores were significantly associated with education levels (rs=0.39, p<0.001), average monthly income (rs=0.28, p<0.001), and age (rs=−0.34, p<0.001). Conclusions. Certain misconceptions are prevalent among patients with diabetes, particularly in those with older age, lower education levels, or lower income. Healthcare providers need to work to eliminate common misconceptions and modify diabetes educational programs accordingly to help patients manage diabetes more effectively.